2018
DOI: 10.1007/s13197-018-3120-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endogenous and exogenous enzymatic treatment of green vanilla beans on extraction of vanillin and main aromatic compounds

Abstract: Endogenous and exogenous enzymatic hydrolysis carried out to obtain vanilla extracts with higher concentrations of vanillin using green vanilla beans. Sequences initiated with freezing of green vanilla beans at - 1 °C for 24 h, followed by endogenous hydrolysis under optimal β-glucosidase activity at 4.2 and 35 °C for 96 h, exogenous hydrolysis with Crystalzyme PML-MX at pH 5.0 and 40 °C for 72 h, and ethanol extraction at 40% (v v) for 30 days. In the proposed method, 200 g of fresh green vanilla beans with 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The first step of the vanilla curing process is killing, and this step aims to promote the reaction of enzymes by destroying the cell structure and halting the further aging of fresh pods [19]. According to the results presented in Table 3, the four different killing methods result in similar component quantities.…”
Section: Different Conditions During the Curing Processmentioning
confidence: 99%
“…The first step of the vanilla curing process is killing, and this step aims to promote the reaction of enzymes by destroying the cell structure and halting the further aging of fresh pods [19]. According to the results presented in Table 3, the four different killing methods result in similar component quantities.…”
Section: Different Conditions During the Curing Processmentioning
confidence: 99%
“…This process usually has four stages: killing, sweating, drying, and conditioning [3]. The killing step is intended to promote enzymatic reactions, destroying the cell structure and stopping the aging of the pods [4]. Regarding the curing method, it has been shown that the conditions of this first stage have a significant effect on the final vanillin content.…”
Section: Introductionmentioning
confidence: 99%
“…The small vanilla seeds present in the exhausted pods still retain a certain economic value because they are added to food products to accomplish consumers” demand for increased naturalness of foods. For this reason, a further separation process can be performed to recover the seeds, leaving a residual by-product without seeds, but still characterized by other volatile compounds as well as varying amounts of vanillin, trapped in the cellular structures of the plant ( 9 ). Thus, the two by-products of vanillin extraction, i.e., vanilla pods with seeds and without seeds, represent a valuable resource for aroma production companies, with potential for repurposing and valorization.…”
Section: Introductionmentioning
confidence: 99%